The Impact of the Credit Rating on Capital Structure in UK Large-cap and Small-cap Firms - Zhou, Weiwei (2019)
This paper uses multiple linear models to examine the impact of the credit rating on the capital structure of Large-cap and Small-cap companies in the UK. The company were select from the FTSE 100 Index and FTSE Small-cap Index respectively, and data collected from 2012 to 2018. The author studies the impact of credit rating in three aspects by establishing three hypotheses: 1) The significance of credit rating. 2) The relationship between credit rating level and company leverage level. 3) How will the company's capital structure change when credit rating close to changes? Regression results show that 1) Credit rating can promote companies to obtain more capital financing. 2) The higher the credit rating level, the lower the company's debt level. 3) When the credit rating is close to change, the company tends to reduce its debt. The conclusion of this paper is consistent with that of other research literature. The author believes that credit rating has a significant impact on the capital structure of a company, whether it is a Large-cap company or a Small-cap company, credit rating should be taken as an essential factor when considering the capital structure.